The changing epidemiology of bacteraemic osteoarticular infections in the early 21st century. (March 2015) - Murillo, O.; Grau, I.; Lora-Tamayo, J.; Gomez-Junyent, J.; Ribera, A.; Tubau, F.; Ariza, J.; Pallares, R.
Abstract: Osteoarticular infections (OAI), which are often associated with bacteraemia, seem to be increasing. We studied all patients with bacteraemia and concomitant OAI: septic arthritis (SA), vertebral osteomyelitis (VOM) or peripheral osteomyelitis (POM), which were seen at our institution (1985–2011). Data were extracted from a prospective protocol of bacteraemia cases recorded. Trends in main findings were considered in five periods. Major antibiotic resistance patterns were studied. A total of 601 cases of bacteraemic OAI, accounting for 1.8% of total bactaeremias, were studied: SA (48%), VOM (40%) and POM (17%). When comparing the 1985–91 and 2007–11 periods, the incidence of bacteraemic OAI increased from 2.34 to 5.78 episodes/100 000 inhabitants per year (p <0.001); and nosocomial and healthcare-related cases increased from 18% to 30% (p <0.001) and from 10% to 25% (p <0.001), respectively. Also, there was an increase of age (median, from 49 to 65 years, p <0.001), patients with comorbidities (23% to 59%, p <0.001), and device-related OAI (7% to 28%, p <0.001). Patterns of OAI were changing over time. Compared with younger patients, older adults (≥ 65 years) had more VOM, prosthetic-joint infections and enterococcal OAI. The percentage of OAI caused by methicillin-susceptible Staphylococcus aureus decreased, while those caused by methicillin-resistant S . aureus, streptococci, enterococci, and Gram-negative bacilli increased. There was a link between certain microorganisms with specific OAI and age of patients. Over the past three decades, bacteraemic OAI increased in association with aging and use of orthopaedic devices. Nosocomial and healthcare-related OAI increased, with a rise in multidrug-resistant bacteria. These trends should be considered when planning diagnostic and therapeutic guidelines for OAI.